2019
DOI: 10.14429/dsj.69.14010
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Behaviour of Austempered Compacted Graphite Iron Perforated Plates

Abstract: In this study, the performance of austempered compacted graphite iron was evaluated to find its suitability as perforated plates used in add-on armour. Perforated compacted graphite plates were subjected to austenitisation at 900 °C for 2 h followed by austempering at 275 and 400 °C for 1 h. The basic plate was fixed at 400 mm away from the perforated plate and armour and then piercing incendiary projectile was shot from a distance of 100 m. It was observed that both 7 mm and 9 mm perforated plates austempered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Further savings could be achieved by utilizing an austempered compacted cast iron (ACGI), which does not possess spheroidal graphite but contains graphite of a short and broad lamellar type due to a lower amount of spheroidisers/nodularisers (cerium and magnesium) [108]. The ACGI compared to ADI material has lower production costs and a lower amount of magnesium, thus reducing the application of CRM.…”
Section: Ballistic Properties Of the Adimentioning
confidence: 99%
“…Further savings could be achieved by utilizing an austempered compacted cast iron (ACGI), which does not possess spheroidal graphite but contains graphite of a short and broad lamellar type due to a lower amount of spheroidisers/nodularisers (cerium and magnesium) [108]. The ACGI compared to ADI material has lower production costs and a lower amount of magnesium, thus reducing the application of CRM.…”
Section: Ballistic Properties Of the Adimentioning
confidence: 99%
“…They also found that the presence of pores inhibited the formation of shear bands on perforated plates. Balos et al [7] evaluated the properties of isothermally quenched ductile iron at different temperatures to determine its applicability as a perforated plate. The study found that 7 mm and 9 mm perforated plates with higher hardness and lower ductility produced by austenitic tempering of isothermally quenched ductile iron at a lower temperature of 275℃ can effectively break the bullet core, thus significantly reducing the penetration ability of the bullet core.…”
Section: Introductionmentioning
confidence: 99%
“…Research gravitates towards the achievement of the best possible mechanical properties while saving the cost and weight of the final product, with a number of benefits by itself. The material that meets many of the above requirements is cast iron [2]. Cast irons have several advantages compared with cast steel such as lower volume shrinkage during solidification and 20-40% lower manufacturing cost, better vibration damping, and wear resistance [3].…”
Section: Introductionmentioning
confidence: 99%